Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.langmuir.7b00244
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surfactants on Sodium Chloride Crystallization in Confinement

Abstract: We study the influence of different surfactants on NaCl crystallization during evaporation of aqueous salt solutions. We found that at concentrations of sodium chloride close to saturation, only the cationic surfactant CTAB and the nonionic surfactant Tween 80 remain stable. For the nonionic surfactant, the high concentration of salt does not significantly change either the critical micellar concentration (CMC) or the surface tension at the CMC; for the cationic surfactant, the CMC is reduced by roughly 2 orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 67 publications
5
45
1
1
Order By: Relevance
“…For instance, the compressive modulus and ionic conductivity of DMAPS‐NaAc (i.e., A 0 D 15 –NaAc 1.2 ) prepared by 15 wt% DMAPS and a NaAc mass ratio of 1.2 was 4.64 MPa and 0.85 S m −1 , respectively. The poly(3‐dimethyl(methacryloyloxyethyl) ammonium propane sulfonate) (PDMAPS) chains can reduce the size of NaAc·3H 2 O crystals due to its surfactant‐like amphiphilic structure in Figure S12 in the Supporting Information . These results prove that crystallization within the hydrogel is a versatile and efficient method to prepare tough gel for salt‐insensitive hydrogel systems.…”
mentioning
confidence: 87%
“…For instance, the compressive modulus and ionic conductivity of DMAPS‐NaAc (i.e., A 0 D 15 –NaAc 1.2 ) prepared by 15 wt% DMAPS and a NaAc mass ratio of 1.2 was 4.64 MPa and 0.85 S m −1 , respectively. The poly(3‐dimethyl(methacryloyloxyethyl) ammonium propane sulfonate) (PDMAPS) chains can reduce the size of NaAc·3H 2 O crystals due to its surfactant‐like amphiphilic structure in Figure S12 in the Supporting Information . These results prove that crystallization within the hydrogel is a versatile and efficient method to prepare tough gel for salt‐insensitive hydrogel systems.…”
mentioning
confidence: 87%
“…Interestingly, the CTAB concentration (0.06 mM) at the inflection point is in good agreement with reported CMC values of CTAB and is also consistent with a decrease of the CMC due to the addition of the electrolyte NaCl. Qazi et al reported that the addition of NaCl to CTAB solution drastically shifts the CMC of CTAB from ~1 mM without salt (water) to ~0.02 mM at high NaCl concentration (5.5 M); this effect may be attributed to the fact that the addition of salts in ionic (cationic) surfactants decreases the electrical double layer thickness of the dissociated and electrically charged head groups, allowing closer approach and prevalence of the attractive van der Waals forces. To validate the finding that the concentration at which the inflection point of the SERS calibration curve (Figure ) coincides with the CMC of CTAB surfactant in a 0.5‐M NaCl solution, the CMC value was also measured using conductometry and fluorescence probing, two methods widely used for CMC determination.…”
Section: Resultsmentioning
confidence: 99%
“…NaCl of 99% purity as supplied by Sigma-Aldrich was used to make an aqueous solution close to solubility [5.5 m, the molality (m) is defined as the number of moles of solute per kilogram of solvent]. Only those surfactants were used that were stable at 5.5 m NaCl solution, as reported in an earlier study (Qazi et al 2017). The two surfactants used were: cationic surfactant cetyltrimethylammonium bromide (CTAB) (critical micelle concentration CMC 0.9E−3 M, 99% purity, Sigma-Aldrich) and a nonionic surfactant Tween 80 (CMC 10 mg/l, proteomics grade purity, Amresco Ltd).…”
Section: Methodsmentioning
confidence: 99%
“…However, apart from wettability enhancers, surfactants can also act as crystallization modifiers (Rodriguez-Navarro et al 2000;Sonin et al 1998;Myatt et al 1994;Qazi et al 2017;Chen et al 2015). Surfactants, by virtue of their ability to adsorb at the interfaces, can preferentially adsorb on selective crystal faces, thereby altering their overall shape, size and other properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation